-(z+5)+(2z+1)=-29

Simple and best practice solution for -(z+5)+(2z+1)=-29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(z+5)+(2z+1)=-29 equation:


Simplifying
-1(z + 5) + (2z + 1) = -29

Reorder the terms:
-1(5 + z) + (2z + 1) = -29
(5 * -1 + z * -1) + (2z + 1) = -29
(-5 + -1z) + (2z + 1) = -29

Reorder the terms:
-5 + -1z + (1 + 2z) = -29

Remove parenthesis around (1 + 2z)
-5 + -1z + 1 + 2z = -29

Reorder the terms:
-5 + 1 + -1z + 2z = -29

Combine like terms: -5 + 1 = -4
-4 + -1z + 2z = -29

Combine like terms: -1z + 2z = 1z
-4 + 1z = -29

Solving
-4 + 1z = -29

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 1z = -29 + 4

Combine like terms: -4 + 4 = 0
0 + 1z = -29 + 4
1z = -29 + 4

Combine like terms: -29 + 4 = -25
1z = -25

Divide each side by '1'.
z = -25

Simplifying
z = -25

See similar equations:

| 3(4)+6k-20=k(4)-k+1 | | 14x+15x= | | 76=2y-28 | | -2.6x=34.84 | | x-0.2x=205000 | | 2x-12/y-4 | | 2x-34=52 | | -6(x+7)-44=5-37 | | 4-2x=5x-5 | | y=-12x+36 | | -22=n/5 | | (u+7)(u+8)=0 | | 3/4*2.10 | | 7(-6-2b)=6-8b | | 20-43=4(x-1)-7 | | 0.6(6e+9f-21g)-7f= | | (-3)/(-4) | | z=13+2(x+y)forx | | 12c=156 | | 11-19c=-18c-19+c | | -14-3m=-m+10 | | -10=-9q+7 | | 10+5f=9f-10 | | 6z-1=3+4z+6 | | (9n+4)+(9n+4)=180 | | 7n+2=-2+8n | | -u=-2u-7 | | 180(n-2)=5400 | | 5w-3=4w | | -9k+5=-10k-4 | | -9k+5=-10j-4 | | -2s-6=-s |

Equations solver categories